Content Analysis: YouTube Responses to President Obama’s “Amazing Grace" Rendition - Brown, Riva; Moody-Ramirez, Mia; Lin, David (Advances in Social Sciences Research Journal, 2016)
This content analysis uses framing to examine the themes and tone of comments on a C-SPAN video posted on YouTube of President Barack Obama singing the opening refrain of “Amazing Grace.” Obama sang an excerpt of the Christian hymn while delivering a eulogy for a Black pastor and state senator who was among nine people gunned down in his churchin 2015. This study incorporates computational techniques, specifically topic modeling. The themes that emerged include God bless America and Obama, Obama is a hypocrite, Obama is a racist, and Obama can sing. Findings show that the most prevalent themes referenced the President’s singing ability and the hypocrisy of a “Muslim” and “supporter of gay marriage” speaking at a funeral for a Christian pastor. Findings also show that a subset of comments was primarily positive yet equally negative and neutral. This study suggests that user-generated content can serve as a catalyst for discussions in a “postracial” society.